Surface designing - Smith, Kitty Myrtle (My University, 1895)
Introduction: It has now been several centuries since the first industrial schools were founded. Since that time the advance in industrial skill has been surprising. In come lines special progress has been made. Formerly France had undisputed sway. Now art is as distributed that each country has its excellence in certain lines so it would be unjust to decide the productions of one nation, on the whole, more perfect than those of another. It might be called a “standing joke” in England that what, in art, is ruined for their market will find a demand here. But art, especially designing, is of recent introduction in the western countries in comparison with the countries of the East where it has been known from time immemorial. Our progress is very gratifying. We are pushing ahead in all directions. Our schools for industrial training, for example are fast improving and multiplying. All over our land young men and women have opportunities for industrial training. At present in the United States attention is being more generally and seriously given to the addition of music and the art of designing in our industrial schools than has formerly been given.
Citation: Smith, Kitty Myrtle. Surface designing. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Industrial schools; Wallpaper; Designing; Theses; Manuscripts (documents)